Evolution and practice pattern in microsurgical breast reconstruction: a European multicenter study - Siegwart, Laura; Grünherz, Lisanne; Weitgasser, Laurenz; Mahrhofer, Maximilian; Abdallah, Nour Abu; Fertsch, Sonia; Wolter, Andreas; Schneider, Laura; Moncher, Johanna; Erdmann, Stella; Bigdeli, Amir Khosrow; Lindenblatt, Nicole; et al. (Journal of plastic, reconstructive & aesthetic surgery, 2025)
Background - This study investigated the evolution and practice pattern in microsurgical breast reconstruction. - Methods - A retrospective multicenter study was conducted including all patients who underwent microsurgical breast reconstruction in 6 European medical centers (January 2010 to December 2019). Patients were grouped according to the flap in the abdominal or alternative group. The patient and outcome data were merged for comparative analysis. Linear regression analysis was used to objectify the evolution in microsurgical breast reconstruction. A multiple mixed effects logistic regression model was applied to identify the predictors for the flap choice. - Results - A total of 4025 microsurgical breast reconstructions were performed in 3344 patients. Among them, 2891 (86%) patients with 3440 flaps were included in the abdominal group and 453 (14%) patients with 585 flaps were included in the alternative group. There was a significant increase (3.7% per year, p = 0.019) in microsurgical breast reconstruction and alternative flaps usage (12.6% per year, p < 0.001). The deep inferior epigastric perforator, transverse musculocutaneous gracilis, and muscle-sparing - transverse rectus abdominis muscle flap were used in >90% cases. The groups differed significantly in characteristics, perioperative, and postoperative parameters. Age, body mass index, radiotherapy, breast reconstruction laterality, the type of mastectomy, and previous implant failure were significant predictors for the flap choice. - Conclusions - This multicenter study outlined a significant increase in microsurgical breast reconstruction and continuous evolution to alternative flaps since 2010. It objectivized the relation of surgical and adjuvant breast cancer therapy on future options in microsurgical breast reconstructions and showed that customized concepts allow each patient in her unique situation to choose natural breast reconstruction.
Online verfügbar: 14. Mai 2025, Artikelversion: 30. Mai 2025
Gesehen am 17.09.2025